Transformasi Digital Humas Bandara Internasional Jenderal Ahmad Yani Semarang Melalui Instagram - Kusuma, Reyhan arya; Umami, Zahrotul (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2024)
Company public relations has a strategic role, especially in the context of communication and information distribution. This research will explore PT Angkasa Pura I's public relations strategy in utilizing Instagram as a digital transformation medium, with the hope of providing a deeper understanding of the company's efforts to communicate and disseminate information through social media. The purpose of this research is to describe PR strategies PT Angkasa Pura I General Ahmad Yani International Airport in disseminating information and communication in the era of digital transformation, especially through social media Instagram @semarangairport. This research uses a qualitative method with a descriptive approach. The theories used are Public Relations, Digital Transformation, Social Media and PESO. The results of this research show that the Public Relations of PT Angkasa Pura I General Ahmad Yani International Airport Semarang has implemented a digital transformation strategy through Instagram by applying the PESO theory (Paid, earned, shared, owned) in disseminating information and communicating with the public.